Rethinking Middle Stone Age lithic tools in North Africa. A structural study of the tool assemblage from level T at El Guettar (Tunisia). - (:unkn) unknown (My University, 2024)
Lithic industries document the activities of prehistoric societies, the technical conditions of their production, collective know-how, and individual skills. In North Africa, few studies examine the technical equipment of the Middle Stone Age (MSA) in this way, a crucial period marked by the emergence of Homo sapiens (315-30 ka). This doctoral thesis contributes to the understanding of technical traditions by adopting an innovative approach to lithic tools, never before applied to North African MSA (NAMSA) assemblages, except for a single Master's thesis.The method used is structural analysis, also called "techno-morpho-functional" or "techno-functional" analysis. It characterizes tools through their structural organization, meaning the arrangement of their « active parts », which interact with materials, and passive parts, which are held or hafted. This method thus allows for proposing functional potentials corresponding to the morphotechnical characteristics identified (cutting, perforation, etc.).The lithic collection analyzed comes from Level T (« tas ») of the El Guettar site in Tunisia, which is extremely rich in tools, famous for the supposed presence of a « cairn » interpreted as a constructed structure but, in fact, poorly known and documented. The application of the structural method yielded multiple levels of results. From a methodological point of view, our approach overcomes some of the biases related to older collections by refocusing the analysis on the tool itself. This represents a reevaluation of the heuristic potential of this collection and, more generally, of older excavated series.The structural analysis covered nearly 700 tools. The technical sphere of the assemblage was precisely characterized through the identification of 14 technotypes of tools that display a common structural organization.The results of this research aim to open new perspectives and serve as a reference work for studies on NAMSA tools. This work thus fo
Keywords: African Research